2019
DOI: 10.5539/ijef.v11n12p1
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure Adjustments and Asymmetric Information

Abstract: The findings of this paper suggest another reason for capital structure adjustments besides the Trade-Off and Pecking Order theories propositions because asymmetric information impacts capital structure changes and deviations only for a quarter whilst stationarity impacts them for 4 quarters, even when controlled. Asymmetric information has been measured by Corwin-Schultz bid ask spread estimator and capital structure target as the mean of debt-to-equity ratio of 262 Nyse non-financial and non-regulated compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In the same line, the signaling theory (Ross, 1977) illustrates that managers with an informational advantage have an incentive to signal their private information through their choice of debt level. Ripamonti (2019) suggests the existence of asymmetric information costs influence American companies to adjust their leverage. The same result is found by Ji et al (2019), who show that firm-level asymmetric information is important determinant of the level leverage of US companies.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the same line, the signaling theory (Ross, 1977) illustrates that managers with an informational advantage have an incentive to signal their private information through their choice of debt level. Ripamonti (2019) suggests the existence of asymmetric information costs influence American companies to adjust their leverage. The same result is found by Ji et al (2019), who show that firm-level asymmetric information is important determinant of the level leverage of US companies.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The authors suggested future research, with portfolio selection according to information asymmetry and asset liquidity balancing. Ripamonti (2019) states that asymmetric information can anticipate the capital structure adjustments. Funaoka and Nishimura (2019) found domestic institutional investors have better information than foreign ones, owing to the fact that institutional investment sentiment and IPO first day returns are positively associated.…”
Section: Stock Pricesmentioning
confidence: 99%
“…Existing related literature has tended to focus mainly on developed countries’ panel sets (Hackbarth et al., 2006 for the case of the United States; for the case of Korea; for a sample of European countries and Ripamonti, 2019 for the US case) while also ignoring the dynamic nature of the risk‐capital structure adjustment nexus. To the best of the authors’ knowledge, few studies, namely Callaghy (1988), Stein and Nissanke (1999), and Chipeta and Deressa (2016), have explored the impact of idiosyncratic and macroeconomic risk on capital structure adjustments in the African markets and even then, they, in addition, to include a limited number of observations, ignored the potential dynamism in the hypothesized link.…”
Section: Introductionmentioning
confidence: 99%